Aseveljien tulkit Jatkosodan monikielinen arki - Kujamäki, Pekka (Suomalaisen Kirjallisuuden Seuran Toimituksia, 2023)
This volume looks at the Finnish-German military alliance (1941-1944) as a translation zone - a multilingual network of military, administrative and civilian encounters that was held together by linguistically versed soldiers and civilians acting as interpreters and translators. It focuses on interpreters and liaison officers of the Finnish Liaison Staff in Rovaniemi, who were assigned to the staffs of the German army units with the task of maintaining communication between the two armies and assisting German troops in their daily matters. Furthermore, attention is paid to Finnish civilians, especially women whose language skills made them candidates for a range of mediation tasks in the German units. The reconstruction of military interpreters' and liaison officers' tasks and mediation agency between the two military cultures is based on their war-time weekly reports, whereas the civilian interpreters' experiences are drawn from a variety of autobiographical accounts, including interviews.